Construction of Evaluation Index System for Training Quality of High-Level Tennis Team - Cai, Qian; Cheng, Yan; Ke, Yong (Frontiers in Psychology, 2022)
The paper established the evaluation index system of training quality of high-level tennis team, which comprising five first-class indexes: work planning evaluation index (i = 4) includes realistic state diagnosis, training goal establishment, specific training content, and training plan formulation; work implementation evaluation index (i = 4) includes training guarantee conditions, training plan implementation, training process monitoring, and training plan adjustment; work monitoring evaluation index (i = 5) includes physical function, physical fitness, sports technique, sports tactics, and sport psychology; the evaluation index of team work management (i = 2) is the team training management and team organization management; and the competition performance index (i = 2) includes the results of large-scale events and the trend of sports talents. Each index of the system was obtained by sorting analysis of radar chart. The weight table of evaluation index was calculated by analytic hierarchy process. Therefore, the evaluation index system of training quality of high-level tennis team constructed in this study aims to provide reference for real-time monitoring, comprehensive evaluation, and diagnostic evaluation of each link of high-level tennis team training.